On approximation of functions by rational functions in weighted generalized grand Smirnov classes - Jafarov, Sadulla Z. (Springer Heidelberg, 2022)
Let G be a doubly connected domain in the complex plane C, bounded by Ahlfors 1-regular curves. In this study the approximation of the functions by Faber-Laurent rational functions in the omega-weighted generalized grand Smirnov classes epsilon(p),theta) (G, omega) in the term of the rth, r = 1, 2 ..., mean modulus of smoothness are investigated.
Keywords: Lebesgue; Polynomials; Curves; Spaces